PENINGKATAN MINAT BACA TERHADAP KREATIVITAS DAYA PIKIR KRITIS DAN KOMUNIKASI SEBAGAI DAMPAK DARI PENGARUH LINGKUNGAN DAN HOBI - Febi Angla Adelia; Tonis, Marian; Indah Ramadhani; intan (Journal of Hospital Administration and Management (JHAM), 2024)
​​Reading interest is a crucial factor in supporting students' academic success, especially for 12th-grade students in their final stage of schooling. This study aims to analyze the reading interest of 12th-grade students at SMA Negeri 7 Pekanbaru by considering variables such as environment, hobbies, communication difficulties, creativity, and critical thinking skills. The environment, including family, school, and community, plays a significant role in shaping reading habits. Additionally, students who consider reading as a hobby tend to have a higher reading interest. Reading also helps overcome communication difficulties by enhancing vocabulary and language skills and supports creativity development by broadening knowledge and fostering new ideas. Furthermore, reading analytical materials trains students to think critically, evaluate information, and make logical decisions. The findings of this study provide an overview of the reading interest of SMA Negeri 7 Pekanbaru students and serve as a foundation for designing effective strategies to promote a literacy culture. This study highlights the importance of the environment, relevant reading materials, and the integration of reading benefits into learning to support the holistic development of students.